EFFECTIVENESS OF WEST SUMATRAN DADIAH ON REDUCING HYPERGLYCAEMIA AND LIPID PROFILE IN DIABETIC RATS - Rinita Amelia; Athif Abyaz Khalil Putra; Arief Rinaldy; Harnavi Harun (PT. Anagata Sembagi Education, 2024)
The high incidence of DM (Diabetes Mellitus) has made diabetes a global health problem that is often associated with other health problems and high treatment costs. For this reason, complementary therapies such as Dadiah are needed. Dadiah is fermented buffalo milk from West Sumatra. This study aims to determine the effectiveness of Dadiah on reducing hyperglycaemia and lipid profile of diabetic model rats. The experimental study used 25 rats divided into five groups. Group 1 was negative control, group 2 was positive control, group 3 was DM rats with Dadiah intervention at a dose of 3g/300gBB, group 4 was DM with metformin 13.5mg/kgBB, and group 5 was DM with a combination of Dadiah and Metformin. After STZ induction, each group was given the intervention for six weeks, and the blood sugar and cholesterol levels were observed. The average decrease in blood sugar levels and cholesterol levels close to the negative control group was obtained in the Dadiah and metformin combination treatment group (P3) with an average blood sugar level of 124.2 mg/dL, total cholesterol level of 78.4 mg/dL, HDL level of 28.2 mg/dL, LDL level of 27.8 mg/dL and triglycerides 113.6 mg/dL. The administration of Dadiah and the combination of Dadiah with Metformin proved to have the highest effectiveness in alleviating hyperglycaemia and hypercholesterolemia in diabetes mellitus model rats.